Deletion of the 5′exons of COL4A6 is not needed for the development of diffuse leiomyomatosis in patients with Alport syndrome. Issue 11 (19th August 2013) - Sá, Maria João Nabais; Fieremans, Nathalie; de Brouwer, Arjan P M; Sousa, Rita; Costa, Fernando Teixeira e; Brito, Maria José; Carvalho, Fernanda; Rodrigues, Márcia; de Sousa, Francisco Teixeira; Felgueiras, Joana; Neves, Fernando; Carvalho, Adelino; et al.
Abstract : Background: Alport syndrome (AS), a hereditary type IV collagen nephropathy, is a major cause of end-stage renal disease in young people. About 85% of the cases are X-linked (ATS), due to mutations in the COL4A5 gene. Rarely, families have a contiguous gene deletion comprising at least exon 1 of COL4A5 and the first exons of COL4A6, associated with the development of diffuse leiomyomatosis (ATS-DL). We report three novel deletions identified in families with AS, one of which challenges the current concepts on genotype-phenotype correlations of ATS/ATS-DL. Methods: In the setting of a multicentric study aiming to describe the genetic epidemiology and molecular pathology of AS in Portugal, three novel COL4A5 deletions were identified in two families with x-linked Alport syndrome (ATS) and in one family with ATS-DL. These mutations were initially detected by PCR and Multiplex Ligation-dependent Probe Amplification, and further mapped by high-resolution X chromosome-specific oligo-array and PCR. Results: In the ATS-DL family, a COL4A5 deletion spanning exons 2 through 51, extending distally beyond COL4A5 but proximally not into COL4A6, segregated with the disease phenotype. A COL4A5 deletion encompassing exons 2 through 29 was identified in one of the ATS families. In the second ATS family, a deletion of exon 13 of COL4A5 through exon 3 of COL4A6 was detected. Conclusions: These observations suggest that deletion of the 5′ exons of COL4A6 and of the common promoter of the COL4A5 and COL4A6 genes is not essential for the development of leiomyomatosis in patients with ATS, and that COL4A5_COL4A6 deletions extending into COL4A6 exon 3 may not result in ATS-DL.